2010
DOI: 10.1186/1471-2458-10-33
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and design of a randomised controlled trial evaluating the effectiveness of an exercise program to improve the quality of life of patients with heart failure in primary care: The EFICAR study protocol

Abstract: BackgroundQuality of life (QoL) decreases as heart failure worsens, which is one of the greatest worries of these patients. Physical exercise has been shown to be safe for people with heart failure. Previous studies have tested heterogeneous exercise programs using different QoL instruments and reported inconsistent effects on QoL. The aim of this study is to evaluate the effectiveness of a new exercise program for people with heart failure (EFICAR), additional to the recommended optimal treatment in primary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
3
0
3
Order By: Relevance
“…Winter et al [71] Data are reported in median Yamamoto et al [72] Study did not report values Zuazagoitia et al [73] It is a protocol registration study …”
Section: Exercise-based Training On Ntprobnpmentioning
confidence: 95%
“…Winter et al [71] Data are reported in median Yamamoto et al [72] Study did not report values Zuazagoitia et al [73] It is a protocol registration study …”
Section: Exercise-based Training On Ntprobnpmentioning
confidence: 95%
“…Diseño. El estudio EFICAR (NCT01033591) 5 es un ensayo clínico aleatorizado multicéntrico que valora la eficacia de un programa de ejercicio en pacientes con ICFSD. Describimos las características basales de los 150 pacientes incluidos.…”
Section: Metodosunclassified
“…La descripción detallada de recogida de datos clínicos, mediciones antropométricas y analíticas, criterios de inclusión y exclusión ya ha sido previamente publicada en el protocolo del estudio EFICAR 5 .…”
Section: Metodosunclassified
“…14,25 The setting for exercise recommendation will vary from self-monitored home exercise to supervised telemetry monitoring with scheduled evaluations to alter and advance therapy. [32][33][34] Furthermore, other factors such as age, race, pharmacologic therapy, depression, sex, income, and comorbidities need to be studied to determine alternative methods to the assessment and prescription of exercise capacity in heart failure. 14,26,[35][36][37][38][39] In addition, the transition from monitored exercise training to home exercise training may also contribute to poor adherence.…”
Section: Exercise As Treatment For Chronic Heart Failurementioning
confidence: 99%
“…8 Exercise training has been shown to improve exercise capacity and quality of life. 33,36,46,47 To date, the evidence shows that the intensity of training does not directly relate to improvements in exercise capacity; therefore, after discussion with the physician, patients should be encouraged to initiate a low-intensity exercise program that can be maintained. 14 become a routine part of their lives.…”
Section: Exercise As Treatment For Chronic Heart Failurementioning
confidence: 99%